SEED SETTING BEHAVIOUR AMONG RESISTANT AND SUSCEPTIBLE GENOTYPES OF GLADIOLUS ( SUSCEPTIBLE GENOTYPES OF GLADIOLUS (GLADIOLUS GLADIOLUS XHYBRIDUS XHYBRIDUS XHYBRIDUS HORT.) FOR FUSARIUM WILT DISEASE - KUMARI, POONAM; RAO, T. MANJUNATHA; KUMAR, RAJIV (The Bioscan, 2016)
Gladiolus (family Iridaceae) is one of the most important flowering geophytes commercially cultivated for cut flower trade in India and abroad. A total of eight intervarietal cross combinations of resistant and susceptible gladiolus genotypes were made and tested at ICAR-Indian Horticultural Research Institute, Hesaraghatta Lake Post, Bengaluru during 2011-2012 with an objective to find out the potentiality of seed setting in different cross combinations.The cross combination ‘IIHRG-12 × Arka Amar’ recorded maximum number of seeds per cross (157.33), early capsule maturity (30.33 days) and highest seed germination (96.89%). The genotype ‘IIHRG-12’ as a female parent in cross combination contributed to higher number of seeds per capsule and per cross. Inclusion of ‘IIHRG-12’ as male parent also has increased comparatively high number of seeds than any of the cross combinations tested.